Developing lightweight structural concrete with enhanced thermal and durability properties through nano-silica and expanded polystyrene integration - Sabry A. Ahmed; Esraa Ebrahem; Ahmed A. M. El-Amir; M. S. El-Feky (Scientific Reports)
Abstract This comprehensive study investigates the development of lightweight structural concrete with enhanced thermal and durability properties by strategically incorporating nano-silica (NS) and expanded polystyrene (EPS) granules. This research aims to design a high-performance concrete composite that can achieve superior thermal insulation, improved water permeability, and maintain structural integrity. NS was strategically incorporated at varying dosages of 0.75, 1, and 1.25% by weight of cement, while EPS was used to replace fine aggregates at 25, 50, 75, and 100% replacement levels. The thermal performance of the concrete mixtures was systematically evaluated using the advanced transient plane source method, providing insights into thermal conductivity, thermal diffusivity, and volumetric heat capacity. The experimental results demonstrate that the addition of NS led to a significant 15% reduction in thermal conductivity, attributed to the filler effect and pozzolanic reactivity of nano-silica. The incorporation of EPS granules exhibited an even more pronounced impact, decreasing the thermal conductivity of concrete by up to 80.5% as the replacement level increased. Notably, the combined use of NS and EPS resulted in a synergistic effect, achieving a remarkable 39–86% reduction in thermal conductivity, 28–71%, and 28–79% reductions in thermal effusivity and diffusivity, respectively, compared to the control mix. Furthermore, the optimal NS content of 1–1.25% was found to enhance the compressive strength by up to 36.5% and reduce the water permeability by 40–52%, indicating improved mechanical and durability properties. These findings highlight the transformative potential of this composite material in developing high-performance, thermally-efficient, and sustainable concrete for energy-efficient buildings, reducing operational energy demands and carbon footprints.